Human plasma fibronectin promotes proliferation and differentiation of odontoblast - TANG, Jia (J Appl Oral Sci, 2017)
OBJECTIVE: To assess the effect of fibronectin (Fn) and porcine type I collagen (PCOL) on odontoblast-like cells in vitro. MATERIAL AND METHODS: Rat odontoblast-like cells (MDPC-23 cells) were inoculated and cultured on Fn-coated or type I collagen-coated substrates. Proliferation assay, alkaline phosphatase activity (ALP activity), mRNA expression of hard tissue-forming markers, and Alizarin red staining were investigated over a period of 10 days. RESULTS: Cells maintained a high proliferation activity on Fn and PCOL even at a low seeding concentration (0.5×10(4)/mL) as demonstrated by CCK-8 assay. The proliferation activity of cells on Fn increases in a concentration-dependent manner while it reached a plateau after 10 µg/mL. Cells adopted long, thin and spindle shape on Fn(10-50) and PCOL. Parallel actin filaments were observed in MDPC-23 cells cultured on Fn and PCOL. ALP activity was markedly up-regulated on Fn and PCOL-coated surfaces. Importantly, gene expression of BSP (Fn10: 2.44±0.32; Fn20: 3.05±0.01; Fn30: 2.90±0.21; Fn40: 2.74±0.30; Fn50: 2.64±0.12; PCOL: 2.20±0.03) and OCN (Fn10: 2.52±0.23; Fn20: 2.28±0.24; Fn30: 2.34±0.21; Fn40: 2.34±0.25; Fn50: 2.20±0.22; PCOL: 1.56±0.16) was significantly enhanced on Fn and PCOL substrates as compared with control; moreover, expression of integrin beta 1 (ITGB1), an ubiquitous cell surface receptor was augmented in Fn(10-50) and PCOL groups simultaneously. In accordance with the ALP activity and gene expression data, calcific deposition in cells grown on Fn(10-50) and PCOL was observed as well. CONCLUSION: Despite the limitation of this study, the findings indicate that a surface coating of Fn enhances the proliferation, differentiation and mineralization of odontoblast-like cells by activation of integrin beta 1 (ITG B1). The promoting effects of Fn on MDPC-23 cells were achieved at a comparatively lower coating concentration than type I collagen (300 µg/mL). Specifically, it is suggested that the optimum coating concentration of Fn to be 10 µg/mL.